0 =- 2 x 5 ) 3x
![0 =- 2 x 5 ) 3x](https://i.ytimg.com/vi/pfRNAbU8Zko/hq720.jpg?sqp=-oaymwE7CK4FEIIDSFryq4qpAy0IARUAAAAAGAElAADIQj0AgKJD8AEB-AHUBoAC4AOKAgwIABABGDogVihlMA8=&rs=AOn4CLAuh1Ycv7gw-CsoJrooj63wQhJgyA)
- 0 =- 2 x 5 )+ 3x
- 0 2x 2 3x 5
- X 2 3x 5 0 quadratic formula
- X 2 3x 5 0 discriminant
- X 2 )( x 5 )( 3x 4 )= 0
- 2 x 3 )- 3x 5 0
- X2 3x 2 x 5 0
- 2 x 3 )+ 3x 0 5 3 4
- 0 2x 2 3x .5 x 2 7x 3
- X 2 3x 5 0 complete the square
- X 2 3x 5 0 factor
- 3x 2 x 5 0 solve
- 3x 2 x 5 0 solve by factoring
- X 2 3x 5 0 quadratic equation